Wake up and smell the coffee: caffeine supplementation and exercise performance—an umbrella review of 21 published meta-analyses - Grgic, J.; Grgic, I.; Pickering, C.; Schoenfeld, B. J.; Bishop, D. J.; Pedisic, Z. (British Journal of Sports Medicine, 2020)
Objective:To systematically review, summarise and appraise findings of published meta-analyses that examined the effects of caffeine on exercise performance.